PENGARUH KARAKTERISTIK DEWAN KOMISARIS DAN KARAKTERISTIK PERUSAHAAN TERHADAP PRAKTIK MANAJEMEN RISIKO PERUSAHAAN (Studi Terhadap Perusahaan yang Terdaftar pada BEI indeks KOMPAS 100 Tahun 2010 s.d 2012) - Ramadhani, Nila; Sari, Ria Nelly; Darlis, Edfan (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
This study aimed to test the influence of the characteristics of commissioners andthe characteristics of the companys board of directors on the companys riskmanagement practices. Characteristics commissioners were used in this study is therisk management committee, board size, the proportion of independent directors andcommissioners educational background, while the characteristics of companies thatuse is reputable auditors, institutional ownership and complexity. The sample usedin this study is a company KOMPAS100 categories listed in the Indonesia StockExchange (BEI) with the observation period 2010-2012. Purposive sampling methodused in the selection of data samples and obtained a sample of 54 companiesselected. This study uses multiple linear regressions. Results from this studyshowed that only the Risk Management Committee, board size and complexity thathave an influence on the companys risk management practices.Keywords: enterprise risk management, board of commissionerâs characteristics,firm characteristics